EXPERIENCE IN A DISTRICT GENERAL HOSPITAL OF ALCOHOL WITHDRAWAL MANAGEMENT COMPARING SYMPTOM TRIGGERED WITH FIXED DOSE REGIMEN IN ACUTE MEDICAL WARD. (8th June 2013) - Conroy, K; Paremal, S; Perez, F; Stidolph, G; Topping, J
Abstract : Introduction: Harmful drinking is endemic in the UK and is a worrying health hazard. It is estimated that up to 24% of the UK adults drink in a hazardous/harmful way. 1 Recent survey shows that up to 35% of the A&E attendance is due to alcohol related, 2 leading into huge financial implications. 3 NICE guidance published in 2010 recommends a symptom triggered regime for patient admitted to hospital with alcohol withdrawal symptoms (AWS). Aims/Background: This Study is designed to compare the effect of symptom triggered regime (STR) using CIWA tool against fixed dose regime (FDR) in patients treated for AWS. Method: Retrospective data collection on 60 patients who were admitted with AWS over a 24 months period. 30 were actively managed in a Gastroenterology Ward where STR was used. The other 30 patients were chosen from General Medical Wards where FDR was used. Results: The mean length of stay for the STR group as calculated was 7.9 days and 10.9 days for the FDR one. 80% of patients in the STR group had a hospital admission of ten days or less where as in FDR group only 46% of patients had this length of stay. The mean total Chlordiazepoxide dose given for the STR group was 264 mg, compared with 501 mg for the FDR group. Conclusion: This audit demonstrates that symptoms triggered regimen leads into a significantly lower total dose of benzodiazepines and a shorter hospital admission. Treatment of symptoms has advantages, both in terms of cost and patient safety.